2021
DOI: 10.1007/s10924-021-02235-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Properties of Starch Plasticized with Glycerol/Urea Mixture

Abstract: The paper presents the results of research on the influence of used plasticizing system on the structural and thermal properties of thermoplastic starch (TPS). The thermoplastic starch granulate was obtained by extrusion of native starch in the presence of a plasticizing system using a twin-screw extruder. Glycerol and urea were used as plasticizers in various proportions. In order to evaluate the effectiveness of the starch plasticization process, changes in its chemical structure were analyzed by infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 41 publications
2
24
1
2
Order By: Relevance
“…Therefore, a small amount of Va-type crystalline residual structure was detected in TPCS films' XRD diffraction pattern. The complete transformation of crystalline usually happens in the first 20 days [11,39,40]. The crystalline structure change by absorbing water molecules agreed with the water absorption result of the pure TPS films.…”
Section: Thermal Analysis For Tpcs Tpcs-c and Tpcs-hc Films Aged For ...supporting
confidence: 78%
“…Therefore, a small amount of Va-type crystalline residual structure was detected in TPCS films' XRD diffraction pattern. The complete transformation of crystalline usually happens in the first 20 days [11,39,40]. The crystalline structure change by absorbing water molecules agreed with the water absorption result of the pure TPS films.…”
Section: Thermal Analysis For Tpcs Tpcs-c and Tpcs-hc Films Aged For ...supporting
confidence: 78%
“…The quantity and sort of plasticizer have a big impact on the PEs’ characteristics. GL is the mainly often used and least expensive plasticizer [ 64 ]. After water, it is one of the most well-known polar compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Paluch et al showed that the efficiency of starch structure breakdown and the formation of stronger polar bonds increased with the use of the hybrid plasticizer combination of glycerol and urea. [19] This combination of starch that has been mixed and processed with plasticizer known as PS is not on its own suitable for any practical applications due to its poor performances. However, TPS has found a wide range of applications within the disposable packaging sector.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the efficiency of starch structure breakdown and the formation of stronger polar bonds increased with the use of the hybrid plasticizer combination of glycerol and urea. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%